Universal Adhesive for Fixed Retainer Bonding: In Vitro Evaluation and Randomized Clinical Trial - Sfondrini Maria Francesca; Gallo Simone; Turcato Benedetta; Montasser Mona A; Albelasy Nehal Fouad; Vallittu Pekka K; Gandini Paola; Scribante Andrea (MDPI, 2022)
This study aims to assess the efficacy of a universal adhesive (Scotchbond Universal, 3M ESPE) (SB) in total-etch mode, compared to a traditional orthodontic primer (Transbond XT Primer, 3M ESPE) (XT Primer), to perform bonding of orthodontic fixed retainers along with the Transbond XT Light Cure Adhesive Paste (3M ESPE). For the in vitro study, a round section wire (Ortosmail Krugg) was bonded using XT Primer for 20 bovine incisors (Group 1) and SB for other 20 (Group 2). Samples were debonded in a universal testing machine applying a tangential force to specimens (crosshead speed of 1 millimeter per minute). Shear bond strength (SBS) and adhesive remnant index (ARI) scores were calculated. For the in vivo study, 100 patients needing upper and lower canine-to-canine fixed retainers after orthodontic treatment were randomly assigned to two groups of 50 participants each, i.e., group 1 (retainer bonding with XT Primer) and group 2 (retainer bonding with SB). Over two years, examinations were carried out monthly, and detachments were registered by considering the teeth and arches affected. In vitro, no statistically significant differences in SBS and ARI scores were demonstrated between the two groups, both showing a mean bond strength of about 12 MPa and major frequency of ARI "2" (>50% remnant adhesive on the enamel). Conversely, a significantly lower failure rate over 2 years was assessed clinically for group 2 in both arches. Independently of the adhesive and arch, incisors reported a significantly higher failure rate than canines. Scotchbond Universal used in total-etch mode could be a valid alternative to the traditional orthodontic Transbond XT Primer.